The Dow Theory: William Peter Hamilton's Track Record Reconsidered - Brown, Stephen J.; Goetzmann, William N.; Kumar, Alok (Journal of Finance, 1998)
Alfred Cowles' test of the Dow Theory apparently provides strong evidence against the ability of Wall Street's most famous chartist to forecast the stock market. Cowles (1934) analyzes editorials published by the chief exponent of the Dow Theory, William Peter Hamilton. We review Cowles' evidence and find that it supports the contrary conclusion. Hamilton's timing strategies actually yield high Sharpe ratios and positive alphas for the period 1902 to 1929. Neural net modeling to replicate Hamilton's market calls provides interesting insight into the Dow Theory and allows us to examine the properties of the theory itself out of sample.